2016
DOI: 10.1007/s40618-016-0572-z
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disruption by perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA)

Abstract: An accumulation of PFOS and PFOA was documented in thyroid cells, and a cytotoxic effect was observed after exposure to extremely high concentrations of these compounds. In environmentally exposed communities and in the general population, the most consistent effect of exposure to PFOA, and to a less extent to PFOS, is the occurrence of hypothyroidism. Women and children appear to be more at risk of developing mild thyroid failure. Pregnant women with circulating thyroid antibodies might be at risk of developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 81 publications
1
61
1
Order By: Relevance
“…TH play a critical role in neurodevelopment (de Escobar et al 2004;Porterfield 1994). PFAS are well-documented thyroid disrupters in humans (Coperchini et al 2017;Webster et al 2016), including in pregnant women (Ballesteros et al 2017;Berg et al 2015;Wang et al 2014;Webster et al 2014). Generally, maternal PFAS levels during pregnancy are associated with shifts in TH levels consistent with hypothyroidism (e.g., elevated thyroidstimulating hormone), which is associated with increased risk for low birth weight (Alexander et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…TH play a critical role in neurodevelopment (de Escobar et al 2004;Porterfield 1994). PFAS are well-documented thyroid disrupters in humans (Coperchini et al 2017;Webster et al 2016), including in pregnant women (Ballesteros et al 2017;Berg et al 2015;Wang et al 2014;Webster et al 2014). Generally, maternal PFAS levels during pregnancy are associated with shifts in TH levels consistent with hypothyroidism (e.g., elevated thyroidstimulating hormone), which is associated with increased risk for low birth weight (Alexander et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PFASs are reported to disrupt thyroid hormone balances by increasing metabolic excretion and inhibiting synthesis of the hormones9). Unlike other persistent organic compounds which preferentially partition into lipid, PFASs are unique as these compounds can resist both water and oil.…”
Section: Perfluoroalkyl Substancesmentioning
confidence: 99%
“…However, not all epidemiological studies have found a negative correlation with PFOS levels in serum (Olsen et al 2003), nor all animal studies (Chang et al 2017). Nevertheless, PFOS has been identified as a thyroid hormone disruptor (ATSDR 2018;Coperchini et al 2017).…”
Section: Introductionmentioning
confidence: 99%